2016
DOI: 10.1080/2162402x.2016.1181252
|View full text |Cite
|
Sign up to set email alerts
|

Programmed death ligand 1 as an indicator of pre-existing adaptive immune responses in human hepatocellular carcinoma

Abstract: It is well known that the aberrant expression of programmed death ligand 1 (PD-L1) on tumor cells impairs antitumor immunity. To date, in hepatocellular carcinoma (HCC), the relationship between PD-L1 expression and host-tumor immunity is not well defined. Here, the expression levels of PD-L1 and CD8(+) T cell infiltration were analyzed by immunohistochemistry (IHC) in formalin fixed paraffin embedded (FFPE) specimens from 167 HCC patients undergoing resection. A significant positive association was found betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 40 publications
5
54
0
Order By: Relevance
“…CD4+ T cells and NK cells are also sources of IFN‐γ in the tumor microenvironment, but the results of IHC analyses showed no correlation between T‐IDO1 expression and CD4+ T cell or NK cell infiltration. These findings are consistent with our reported quantitative PCR results in freshly resected HCC tissues, which showed no correlation between IFNG and CD4 or CD56 at the mRNA level . This might be due to NK cells seldom infiltrating into HCC, and there is not only Th1 in CD4+ T cells in the HCC microenvironment …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…CD4+ T cells and NK cells are also sources of IFN‐γ in the tumor microenvironment, but the results of IHC analyses showed no correlation between T‐IDO1 expression and CD4+ T cell or NK cell infiltration. These findings are consistent with our reported quantitative PCR results in freshly resected HCC tissues, which showed no correlation between IFNG and CD4 or CD56 at the mRNA level . This might be due to NK cells seldom infiltrating into HCC, and there is not only Th1 in CD4+ T cells in the HCC microenvironment …”
Section: Discussionsupporting
confidence: 92%
“…Patients with low levels of T‐IDO1 expression were older than patients with high levels, which could be explained by decreased production of cytokines and lower per‐cell cytotoxicity, resulting from innate immunosenescence . Thus, overexpression of the immunosuppressive molecule IDO1 by tumors positively correlates with enhanced antitumor immunity, and our seemingly contradictory conclusion has been supported by many previous studies in other tumors …”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Consistently, our IHC results showed that PD-L1 expression in TC is mainly detected in areas surrounded by gatherings of immune cells in gastric cancer tissues, with correlations between TC PD-L1 and more infiltration of CD8 þ T cell confirmed by the Spearman test. Patients with PD-L1 þ tumor cells and CD8 More T cells have the best prognosis compared to other groups, indicating an adaptive immune status existing in gastric cancer patients, consistent with reports in melanoma and hepatocellular carcinoma (39,40), although PD-L1 has been reported to correlate with the worse survival of gastric cancer patients (14). A possible explanation for the contrary results is the different patient populations enrolled.…”
Section: Discussionsupporting
confidence: 81%